Analisis Harga Pokok Produksi Dan Harga Jual UKM Tempe Ceria Di Desa Sumber Mulya Kecamatan Simpang Raya: Analysis of Cost of Goods Produced and Selling Price of UKM Tempe Ceria in Sumber Mulya Village, Simpang Raya District - Rustiawati, Yuni; Ruhu, Rubia; Enteding, Trianto; Saida, Susanty; Bidullah, Taufik (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2024)
The agricultural sector has a strategic role in the national economy that provides industrial raw materials, and absorbs labor, on a national and local scale. One of them is the developing Small and Medium Enterprises (SMEs), namely the Ceria tempeh chips business in Sumber Mulya village, Simpang Raya sub-district. So that the need for research is carried out to know the determination of production prices and selling prices of tempeh chips SMEs. This research was conducted in Sumber Mulya Village, Simpang Raya Subdistrict using the Full Costing Method to determine the cost of production and the Full Cost Pricing Method to determine the selling price of tempeh chips. The results of the research obtained, namely, the determination of the selling price set by the Small and Medium Enterprises (SMEs) of ceria tempeh chips still uses the selling price method based on market prices in general without calculating the selling price with the full costing method. in addition, the selling price set by SMEs of Ceria tempeh chips is Rp. 27,500 / pack while calculating the selling price using Cost Plus Pricing is Rp. 13,500 / pack. The difference between the selling price set by SMEs ceria tempeh chips and Cost Plus Pricing selling price is Rp. 14,000. so that the profit is twice as big as the selling price using Cost Plus Pricing